(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The subject of the analysis in this paper is the examination of the legal regulation of electronic money in international monetary law. In this context, the first part of the paper points to the influence of electronic media on the development of international monetary law, which is today most evident in the emergence of electronic money that redefines traditional money functions. The author therefore deals with the argumentative search for a potential answer to the question of whether the role of the issuer of electronic money should be found in the central bank, the government, the banking system or an international monetary legal entity such as International Monetary Fund, which operates outside the framework of the national monetary jurisdiction in view of the extraterritorial effects of using such money in the financial market. In further text, attention is paid to the advantages and disadvantages of the use of electronic money in commercial transport, the redefinition of state nominalism (lex monetae) and a different understanding of monetary aggregates. The author conclude that international monetary legislator is expected to solve the problem of discrepancy between the globalized financial market, on the one hand, and the fragmentation of the monetary system, on the other hand (which not include monetary union with centralized monetary policy) in the future period.